Maternal Attributions of Infant Behavior and Parenting in Toddlerhood Predict Teacher-Rated Internalizing Problems in Childhood. (21st December 2018) - Wagner, Nicholas J.; Gueron-Sela, Noa; Bedford, Rachael; Propper, Cathi
Abstract : Social-information-processing theories of parenting posit that parents' beliefs and attributions about their children's behaviors contribute to how parents interact with their children. The purpose of this study was to examine the associations between negative parenting attributions in infancy, harsh-intrusive parenting in toddlerhood, and children's internalizing problems (IPs) in early childhood. Using data from a diverse longitudinal study ( n = 206), the current study used a structural equation modeling approach to test if mothers' negative attributions measured at 6 months predicted teacher ratings of children's IPs in 1st grade, as well as the extent to which observed harsh-intrusive parenting behaviors measured at ages 1, 2, and 3 years mediated this link. Maternal negative attributions in infancy predict more IPs in 1st grade, but this link becomes nonsignificant when observed harsh-intrusive parenting is included as a mediator. A significant indirect effect suggests that harsh-intrusive parenting mediates the association between early negative attributions and eventual IPs. Findings from this study identify harsh-intrusive parenting behaviors as one potential mechanism through which the effects of early attributions are carried forward to influence children's IPs. The developmental and clinical implications of these findings are discussed.